CODESRIA Bulletin Online, No. 13, August 2022 - ‘Crisis? What Crisis?’ A Response to René Odanga’s Missive on African Studies - Chachage, Chambi (CODESRIA Bulletin, 2022)
‘But if in fact there is a crisis, whose crisis is it and what is its trajectory?’ – Paul Tiyambe Zeleza[1] Sometime in April over a decade ago the then President of South Africa popularised the rhetorical question: ‘Crisis? What Crisis?’[2] In a tone of denialism, Thabo Mbeki dismissed the post-election crisis in Zimbabwe. Various media echoed it over and over again.[3] K. René Odanga seems to ask such a question but regarding a field of study. In a well-received article published in the CODESRIA Bulletin, he contends: ‘There is no crisis in African Studies.’[4] Of course, he qualifies his controversial statement with a cautiously crafted preamble: ‘I want to choose my words carefully for the profit of clarity. For I have looked upon the scene and seen what I have seen.’[5] He is also careful enough to clarify all this by way of contextualisation: There never has been. There are no debates. No discourses. There is only white supremacist power maintaining its grip as a system and as the main arbiter of the African people and, by the transitive effect, the African reality. And as many well-meaning individuals and organisations fight to dislodge this power from its erstwhile throne, it reasserts itself through any number of wiles, generating and perpetuating ostensible crises.[6] Echoing Zeleza – the author of Manufacturing African Studies and Crises and drafter of ‘The Perpetual Solitudes and Crises of African Studies in the United States’ – Odanga seems to both validate and invalidate the ongoing crises in this interdisciplinary field of study.[7] However, he goes a step further by dismissing, albeit sympathetically, voices of African scholars involved in decolonising African Studies. In such dialectics, African voices are subsumed if not muted: And what is with this insistence that we must engage with the conversation anyway? It is the misrepresentation of Euro-America’s monologue as dialogue. For it is difficult to show that Euro-American scholarship on Africa ever intended to speak with Africans about their Africa. Worse, that Africa should ever talk back. This monologue has been cunningly disguised as a ‘crisis’.[8] Touché. Odanga captures a dialogue-cum-monologue. Echoing Toni Morrison[9], he concludes: So now, we have been turned into perennial faultfinders, perpetual nitpickers and, in some instances, ingrate interlopers. Before we can embark on our own work, we are inundated by that of others which purports to speak with even clearer voice. And we must ‘debate’ them. We must go through their profitless product with a fine-tooth comb, a process deliberately designed and ingeniously engineered to break both our picks and our backs, but disingenuously disguised as ‘scholarly discourse’. Ridiculous.[10] Ouch! It is surely a Sisyphean task for African scholars to respond to the West’s never-ending dismissing of ‘the Rest’.[11] The burden is even heavier when this dismissal comes from those Oyekan Owomoyela decried way back in 1994: ‘With Friends Like These … A Critique of Pervasive Anti-Africanisms in Current African Studies Epistemology and Methodology.’[12] But this burden – indeed pain – that Odanga and his fellow signatories of a missive to African Studies Review (ASR) and African Studies Association (ASA) carry ought not make us lose sight of the other side of scholarship on Africa.[13] Whether it is called African Studies, Pan-African Studies, or any other iterative name, the study of Africa will continue to have a rich history beyond Africanist monologues.[14] What is vital is to ensure that such crises don’t impede it. African scholars are bound by default to the study of Africa irrespective of whether they specialise in the social or natural sciences.[15] In whatever we do in our scholarship, Africa is implicated for better or worse.[16] We cannot wake up one morning like Emeritus Professor of Politics in the School of Social Sciences at the University of New South Wales Gavin Kitching did in 2000 and declare: ‘In a word, I gave up African studies because I found it depressing.’[17] You can run all you want to global health, medical humanities, or any other field of study that purports to be universal and critical but Africa and, by implication African Studies, will catch up with you there like your own shadow. That is how pervasive the African continent is to anyone who is born of it. Kwame Nkrumah was probably acutely aware of this when he declared: ‘I am not African because I was born in Africa, but because Africa was born in me.’[18]​ What Odanga is wary of is something that has left many African scholars worn out. But it is a task that will continue as long as coloniality in all its virulent iterations negatively impacts everything African – people, scholarship, livelihood and so forth. Abiola Irele captured it like this: In its polemical stance, then, African discourse presents itself as a thorough-going deconstruction of the Western image of the Native, the Black, the African.[19] Irele refers to this as a ‘minority discourse.’[20] The people of Africa were well placed to develop this African discourse because of being represented as the ‘absolute other’. Thus it ‘marks the extreme position of dissent from the systematising, totalising thrust of the Western imperialist system.’[21] ‘This dissent has force not only in its bearing upon the application of the Western conceptual system in its concrete effects to our historical situation,’ he notes, ‘but upon the structure and the universalist ambitions of the system itself.’[22] Dissident responses, such as Odanga’s and his cosignatories, one may add, are not mere monologues disguised as dialogues. Rather, they are diatribes infused with agency – the very African agency that Odanga wants expunged from ‘all scholarly conversation until such time as it is not taken as a trait yet unfound in the African.’[23] Irele comes handy again about the imperativeness of our responding: A conditioning factor of African response has thus been, quite simply, an acute racial consciousness in direct reaction to the negativizing premises of Western racist ideology. Thus African discourse has been historically projected in an essentially adversarial posture and has thus assumed a polemical significance. In whatever accents African response has been given expression, whether in an openly combative form or a discreetly pathetic one – with gradations in between – the discursive project has taken the form of an ongoing, principled dispute with the West over the terms of African/Black existence and, ultimately, of being.[24] Understandably, Odanga queries such a preoccupation even though he is invested in it too: Whatever debates surround and pierce the field of African Studies, its history, methodology, epistemology, theory, economic viability within the academy and praxis, political or sociocultural utility, even disciplinarity, they all percolate around the same matter, the subject of study – the African. And while many scholars grapple with the question of the origin, scope, and methodology of the field, whether they know it or not, the question they are engaging with, is the African themself. Even the various epochs into which African Studies is periodised by scholars represent not just the ongoing politico-academic contexts and discourses of the day but, more significantly, the place of Africans and the evolution of the outlook towards them by the world: where ‘the world’ subsumes both the non-African academic and the African academic, the latter of whom is carrying out an exercise of self-study and reflection – whether they like it or not.[25] Counter discourses, however, will polemically attempt to put the African at the centre as long as racism and global apartheid marginalise Africans. Ideally, we should live in the world that Odanga envisages, one in which African humanity is not questioned or, in the parlance of Emmanuel Eze, has to be achieved.[26] A post-racial world in which African agency is taken for granted, by default, rather than as a thing that ‘must be searched for then discovered; debated, defined, redefined, then rethought; edited and reviewed; in a way not done for any other peoples.’[27] Until then we will continue to address the question of the place of the African being. Letting go is still a pipe dream. The West, even through seemingly benevolent white Africanists who pervade the field of African Studies, is guarding jealously the perks of a global racialist order. Delinking, in the parlance of Samir Amin, remains a farfetched solution for scholars in both African and Euro-American universities as academic institutions and disciplines across the ‘West-Rest’ divide are still more or less beholden to what V.Y. Mudimbe refers to as the ‘Western epistemological order.’[28] And dialoguing, for the likes of Odanga, is monologuing. Hence what is still needed is a sustained pushback against this system. ‘In this sense,’ Irele aptly sums up, ‘the discourse of Africanism as elaborated by Black intellectuals on both sides of the Atlantic must be seen as a reinscription of an antecedent Western monologue on Africa and the non-Western world, its displacement and transformation by a new, assertive self-expression on the part of a subjugated and previously voiceless humanity.’[29] Coming out of the Babylon system is as ontological as it is epistemological. Bob Marley saw it when he sang: We refuse to be What you wanted us to be We are what we are That’s the way it’s going to be.[30] Notes [1] Zeleza, Paul Tiyambe, 1997, ‘The Pasts and Futures of African Studies and Area Studies’, Ufahamu: A Journal of African Studies, Vol. 25, No. 5. https://escholarship.org/content/qt2230b25k/qt2230b25k.pdf?t=mniolv. 15 August 2022. [2] The Sydney Morning Herald, April 13, 2008, ‘Crisis? What crisis, says Mbeki on way to summit’. https://www.smh.com.au/world/crisis-what-crisis-says-mbeki-on-way-to-summit-20080413-gds9d2.html. 15 August 2022. [3] Zimbabwe Independent, April 16, 2008, ‘Crisis? What Crisis?’ https://allafrica.com/stories/200804180920.html; The Economist, April 17, 2008, ‘Crisis? What Crisis?’. https://www.economist.com/middle-east-and-africa/2008/04/17/crisis-what-crisis. 15 August 2022. [4] Odanga, K. René, 2022, ‘(In)Validating Crises in African Studies: Certain Reflections on Disciplinary Stagnancy’, CODESRIA Bulletin Online, No. 12, p. 2. https://journals.codesria.org/index.php/codesriabulletin/article/view/2210/2163. 15 August 2022. [5] Odanga, ‘(In)Validating Crises in African Studies’, p. 2. [6] Odanga, ‘(In)Validating Crises in African Studies’, p. 2. [7] Zeleza, Paul Tiyambe, 1997, Manufacturing African Studies and Crises, Dakar: CODESRIA; Zeleza, Paul Tiyambe, 1997, ‘The Perpetual Solitudes and Crises of African Studies in the United States’, Africa Today. Vol. 44, No. 2, pp. 193–210. http://www.jstor.org/stable/4187161. 15 August 2022. [8] Odanga, ‘(In)Validating Crises in African Studies’, p. 5. [9] Espinoza, Jeanette C., 2022, ‘Toni Morrison Was Right – The Very Serious Function of Racism is a Distraction’, An Injustice!. https://aninjusticemag.com/toni-morrison-was-right-the-very-serious-function-of-racism-is-a-distraction-f39b0faa8fe2. 15 August 2022. [10] Odanga, ‘(In)Validating Crises in African Studies’, p. 5. [11] Chachage, Chambi, 2019, ‘From Ghettoizing to Gentrifying African Studies,’ Africa Blogging, January 7, 2019. https://blogging.africa/general/from-ghettoizing-to-gentrifying-african-studies/. 15 August 2022. [12] Owomoyela, Oyekan, 1994, ‘With Friends Like These … A Critique of Pervasive Anti-Africanisms in Current African Studies Epistemology and Methodology’, African Studies Review, Vol. 37, No. 3, pp. 77–101. [13] Flaherty, Colleen, 2022,‘Retract or Attack?’, Inside Higher ED, May 24, 2022. https://www.insidehighered.com/news/2022/05/24/black-scholars-demand-retraction-autoethnography-article. 15 August 2022.; Mohammed, Wunpini; Kalinga, Chisomo; Odanga, K. René; Zelzer, Ruby; Ogunmodede, Chris Olaoluwa; Asani, Furaha and Agbakoba, Dr Ruth Ngozika, 2022, ‘Open Letter to African Studies Review Journal Editorial Board: Call for Retraction of Article “African Studies Keyword: Autoethnography”,’ May 19, 2022. https://docs.google.com/forms/d/e/1FAIpQLSdKo9OgNuU0DcYMBRbuTvv2wu-sJE3StYIIaFuclGJiDevx8g/viewform. 15 August 2022. [14] Chachage, Chambi, 2007, ‘Bringing African Studies Back to Africa: Beyond the “African-Africanist” Divides’, Paper presented at the 2nd Africa-Europe Group for Interdisciplinary Studies (AEGIS) Conference on African Studies (ECAS) at the African Studies Centre, Leiden, the Netherlands (July 11–14, 2007). https://www.academia.edu/38044084/Bringing_African_Studies_Back_to_Africa_Chambi_Chachage_1_doc. 15 August 2022. [15] Zeleza, Paul Tiyambe, ed., 2006, The study of Africa Vol. 1: Disciplinary and Interdisciplinary Encounters, Dakar: CODESRIA; Zeleza, Paul Tiyambe, ed., 2006, The Study of Africa Volume 2: Global and Transnational Engagements, African Books Collective, 2006; West, Michael O. and Martin, William G., 1997, ‘A Future with a Past: Resurrecting the Study of Africa in the post-Africanist Era’, Africa Today, Vol. 44, No. 3, pp. 309–326; Martin, William G. and West, Michael Oliver, eds., 1999, Out of one, many Africas: Reconstructing the study and meaning of Africa, University of Illinois Press; Falola, Toyin, 2017, Africanizing knowledge: African studies across the disciplines, Routledge; Bates, Robert H., Mudimbe, V.Y. and O’Barr, Jean, eds., 1993, Africa and the disciplines: The contributions of research in Africa to the social sciences and humanities, University of Chicago Press. [16] Nwoye, Augustine, 2022, African psychology: The emergence of a tradition, Oxford University Press; Ratele, Kopano, 2019, The World Looks Like This From Here: Thoughts on African Psychology, Wits University Press; Mavhunga, Clapperton, 2017, What do science, technology, and innovation mean from Africa?, The MIT Press; Friederici, Nicolas, Michel Wahome, and Mark Graham, 2020, Digital entrepreneurship in Africa: How a continent is escaping Silicon Valley’s long shadow, The MIT Press; Bangura, Abdul Karim, 2011, African mathematics: From bones to computers, University Press of America; Eglash, Ron, 1999, African fractals: Modern computing and indigenous design, Rutgers University Press; Musonda, Francis B., 1990, ‘African archaeology: Looking forward’, African Archaeological Review, Vol. 8, No. 1, pp. 3–22. [17] Kitching, Gavin, 2000, ‘Why I gave up African studies.’ Mots Pluriels, Vol. 16, p. 24. https://motspluriels.arts.uwa.edu.au/MP1600gk.html. 15 August 2022; Routledge, ‘Gavin Norman Kitching’. https://www.routledge.com/authors/i10561-gavin-kitching. 17 August 2022; Macamo, Elísio, 2021, ‘Unmaking Africa – the Humanities and the Study of What?’, History of Humanities, Vol. 6, No. 2, pp. 381–395. [18] Arthur, Tori Omega, 2022, ‘“We Bring Home the Roots”: Black Women Travel Influencers, Digital Culture Bearing, and African Internationalism in Instagram’, Social Media + Society 8, No. 2., p. 7. https://journals.sagepub.com/doi/full/10.1177/20563051221103843. [19] Irele, Abiola, 2001, The African imagination: literature in Africa & the black diaspora, Oxford University Press, p. 72. [20] Irele, The African imagination, p. 72. [21] Irele, The African imagination, p. 72. [22] Irele, The African imagination, p. 72. [23] Odanga, ‘(In)Validating Crises in African Studies’, p. 3. [24] Irele, The African imagination, p. 69. [25] Odanga, ‘(In)Validating Crises in African Studies’, p. 2. [26] Eze, Emmanuel C. 2013, Achieving our humanity: The idea of the postracial future, Routledge. [27] Odanga, ‘(In)Validating Crises in African Studies’, p. 2. [28] Amin, Samir, 1990, Delinking: Towards a polycentric world, Zed Books; Mudimbe, V.Y., 1988, The invention of Africa: Gnosis, philosophy, and the order of knowledge, Indiana University Press, p. 10. [29] Irele, The African imagination, pp. 72–73. [30] ‘Babylon System’, YouTube video, 4:37, posted by ‘Bob Marley’, May 30, 2020. https://www.youtube.com/watch?v=mzv1EI5gDnE. 15 August 2022; Bob Marley, Twitter post, August 2020, 12:00a.m., https://twitter.com/bobmarley/status/1292204002948591618?s=20&t=tm54kmLob-jqZIBOu9-JVg. 15 August 2022.